EDUCATION OF REFLECTIVE SKILLS IN FUTURE TEACHERS AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM - Gerasimova О. І. (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the different scientists’ views to investigating problem, specifice the content of the concept "reflexive skills".